DETERMINANT FACTORS OF RURAL SETTLEMENT VULNERABILITY TO SLUM DEVELOPMENT IN BONE BOLANGO REGENCY - Abas, Amir; Fosterharoldas Swasto, Deva (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
At first, slum settlements were often identified with urban areas, but as time progresses, this phenomenon also begins to spread to rural areas. On the other hand, rural settlement areas are characterized by dominant activities in the agricultural sector, involving the management of natural resources such as land and water. Based on the results of qualitative research with a deductive approach that mentions the factors causing the vulnerability of slum settlements in the Settlement Area of the Village, located in the Bone Bolango Regency, it can be concluded that there are two groups of factors that affect these conditions: physical factors and non-physical factors. Physical factors including waste disposal, environmental roads, drainage, uninhabitable building conditions, and environmental health problems such as dengue fever play a crucial role in creating the vulnerability of slum settlements. Poor infrastructure conditions and lack of attention to sanitation make these settlements vulnerable to various environmental and health problems. Meanwhile, non-physical factors, including the perceptions of the government and society as well as the social and cultural factors of the community, also have significant influence. Inadequate perceptions of the government and society regarding the importance of improving infrastructure and sanitation, as well as social and cultural factors influencing decisions on the development and management of settlements, also contribute to the vulnerability of slum settlements.